SUSTAINABLE DEVELOPMENT AND NATIONAL SOCIAL-ECOLOGICAL POLICY ANDER GLOBALIZATION - Suleymanov, Gunduz (Научно-просветительский журнал "Наставник", 2020)
In the article are studied the social-ecological situation and philosophical essence of the concept of sustainable human development in Azerbaijan. Analyzed reasons of formation this conception and has been cleared up definition of those factors which cause the necessity of this concept. Is noted president I.Aliyev`s politic in ensuring the ecological safety of the republic.